Eye health knowledge among basic level science and health education teachers in Solukhumbu district of Nepal - Basnet, Pushpa Babu; Budhathoki, Chitra Bahadur (Journal of Health Promotion, 2022)
Prior studies showed that school teachers have an important role in controlling blindness at the community level. A school eye health promotion program is essential because it helps cover health services for children in the community. The study aimed to assess the factors of eye-health problems and eye-health knowledge at the basic level of school teachers at the primary level of eye health problems and care. A cross-sectional study design was implemented with a self-administered questionnaire. A total of 292 health and science basic-level school teachers have been selected from the Solukhumbu district. The sample size was determined by Slovin’s formula. Data were analyzed using the IBM Statistical Package for the Social Sciences (SPSS) V20. The proportion of teachers knowing eye health problems and care of children is higher among teachers having qualifications at master level or above (mean rank = 179.99) than the bachelor level (mean rank =146.30), grade twelve (mean rank =149.06) and grade ten (mean rank =116.91) which was statistically significant (p<0.05. The study concluded that the level of qualification of the teacher was significantly associated with knowledge of the eye-health. Hence teachers who have low qualifications should be trained in the eye-health.